2018
DOI: 10.1002/jlb.5mir0917-351r
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ orchestrates tumor elimination, tumor dormancy, tumor escape, and progression

Abstract: Tumor immunoediting consisting of three phases of elimination, equilibrium or dormancy, and escape has been supported by preclinical and clinical data. A comprehensive understanding of the molecular mechanisms by which antitumor immune responses regulate these three phases are important for developing highly tailored immunotherapeutics that can control cancer. To this end, IFN-γ produced by Th1 cells, cytotoxic T cells, NK cells, and NKT cells is a pleiotropic cytokine that is involved in all three phases of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 52 publications
2
55
0
Order By: Relevance
“…For immune cells, IFNγ signaling activates antigen‐presenting cells (APCs) to upregulate the expressions of cytokines (IL‐12 and IL‐18) and costimulatory molecule CD86 that enhance Th1 differentiation and cytotoxic T lymphocyte (CTL) function . Furthermore, those APCs activated by IFNγ increase the expression of MHC molecules and components of the antigen‐processing machinery.…”
Section: The Role Of Ifnγ In Immune Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…For immune cells, IFNγ signaling activates antigen‐presenting cells (APCs) to upregulate the expressions of cytokines (IL‐12 and IL‐18) and costimulatory molecule CD86 that enhance Th1 differentiation and cytotoxic T lymphocyte (CTL) function . Furthermore, those APCs activated by IFNγ increase the expression of MHC molecules and components of the antigen‐processing machinery.…”
Section: The Role Of Ifnγ In Immune Eliminationmentioning
confidence: 99%
“…For immune cells, IFNγ signaling activates antigenpresenting cells (APCs) to upregulate the expressions of cytokines (IL-12 and IL-18) and costimulatory molecule CD86 that enhance Th1 differentiation and cytotoxic T lymphocyte (CTL) function. [26][27][28] Furthermore, those APCs activated by IFNγ increase the expression of MHC molecules and components of the antigen-processing machinery. In addition, IFNγ induces a number of signals in T cells to enable T cell function effectively, while the loss of IFNγ signaling pathways in T cells dampens T cell responses and allows tumor growth and persistence.…”
Section: Immune Eliminationmentioning
confidence: 99%
“…Immunotherapeutics that target disseminated cancer dormancy may aid to control or eliminate cancer state. In this view, treatment modalities that induce or amplify the CTL immune response or abrogate CTL immunosuppression mediated by cancer cells might be beneficial to confine or eradicate metastatic cells [112]. Meanwhile, an association of human Tregs, neutrophils and inflammatory mediators such as interferon-gamma (IFNγ) are rather context-dependent [109].…”
Section: Cancer Immune-mediated Dormancymentioning
confidence: 99%
“…Immunotherapeutics that target disseminated cancer dormancy may aid to control or eliminate cancer state. In this view, treatment modalities that induce or amplify the CTL immune response or abrogate CTL immunosuppression mediated by cancer cells might be beneficial to confine or eradicate metastatic cells [112]. Dormancy state induced by the elimination of primary tumor can be avoided by a "recombinant T cell receptor ligand therapy", dosing days in advance to tumor resection and lasting throughout the whole treatment course, that is a highly speculative therapy [113].…”
Section: Cancer Immune-mediated Dormancymentioning
confidence: 99%
“…Production of IFNs is a hallmark of immunotherapeutic antitumor activity [35,36]. In the studies reported here we measured the production of IFN-γ in mice implanted with A20 tumor cells and injected with 1 × 107 pfu of T1012G, T2850, or T3855 oHSV.…”
Section: The Mechanisms Of Anti-tumor Effects Of Ohsvs Produced and Tmentioning
confidence: 99%